Pseudogenization of the cntQ permease confers distinct yersinopine-metal uptake selectivity in Yersinia species - Clémentine Laffont; Elizabeth Pradel; Laurent Ouerdane; Amélie Dewitte; Nicolas Oswaldo Gomez; Mathilde Tribout; Catherine Brutesco; Romé Voulhoux; Ryszard Lobinski; Florent Sebbane; Pascal Arnoux (BioMetals, 2026)
Yersinopine, a nicotianamine-like metallophore, was recently identified through biochemical analyses, but its in vivo production and functional role remain uncharacterized. In Yersinia pseudotuberculosis and its recent descendant Yersinia pestis , the cnt operon ( cntPQRLMI ) putatively encodes the biosynthesis and transport of yersinopine. In Y. pestis , however, two frameshift mutations disrupt cntQ , which encodes the predicted permease for yersinopine-metal complexes. This pseudogenization raises critical questions about the functional relevance of yersinopine in these closely related species. Here, we show that cnt operon expression is repressed by the zinc uptake regulator Zur and that both Y. pestis and Y. pseudotuberculosis secrete yersinopine under zinc-limited conditions. Unexpectedly, the operon mediates iron uptake in Y. pseudotuberculosis but supports zinc acquisition in Y. pestis . Moreover, targeted disruption of cntQ in Y. pseudotuberculosis shifts metal specificity from iron to zinc, mimicking the Y. pestis phenotype. Collectively, our results suggest that a single pseudogenization event could rewire metal uptake specificity. Our findings illustrate how evolutionary genome reduction can reshape bacterial physiology.

Correction to: Exploring heat risk in pregnant women: do environmental and social inequalities amplify heat exposure? - Lucie Adélaïde; Aurélie Nakamura; Ariane Guilbert; Stéphanie Vandentorren; Morgane Stempfelet; Ian Hough; Emie Seyve; Guy Launoy; Ludivine Launay; Marie-Aline Charles; Cécile Chevrier; Christine Monfort; et al. (International Journal of Biometeorology, 2025)

Exploring heat risk in pregnant women: do environmental and social inequalities amplify heat exposure? - Lucie Adélaïde; Aurélie Nakamura; Ariane Guilbert; Stéphanie Vandentorren; Morgane Stempfelet; Ian Hough; Emie Seyve; Guy Launoy; Ludivine Launay; Marie-Aline Charles; Cécile Chevrier; Christine Monfort; et al. (International Journal of Biometeorology, 2025)

On the supra-linearity of the relationship between air pollution, mortality and hospital admission in 18 French cities - Vérène Wagner; Mathilde Pascal; Magali Corso; Anna Alari; Tarik Benmarhnia; Alain Le Tertre (International Archives of Occupational and Environmental Health, 2023)

Changes in the temperature-mortality relationship in France: Limited evidence of adaptation to a new climate - Mathilde Pascal; Vérène Wagner; Magali Corso (International Journal of Biometeorology, 2023)

Influence of temperature on mortality in the French overseas regions: a pledge for adaptation to heat in tropical marine climates - Mathilde Pascal; Vérène Wagner; Magali Corso; Robin Lagarrigue; Jean-Louis Solet; Elise Daudens; Lydéric Aubert; Cyril Rousseau (International Journal of Biometeorology, 2022)

Evolving heat waves characteristics challenge heat warning systems and prevention plans - Mathilde Pascal; Robin Lagarrigue; Anouk Tabai; Isabelle Bonmarin; Sacha Camail; Karine Laaidi; Alain Le Tertre; Sébastien Denys (International Journal of Biometeorology, 2021)

Global Change: a Public Health Researcher’s Ethical Responsibility - Mathilde Pascal; Pascal Beaudeau; Sylvia Medina; Nikita Charles Hamilton (Current Environmental Health Reports, 2019)

Temperature-related mortality impacts under and beyond Paris Agreement climate change scenarios - Ana Maria Vicedo-Cabrera; Yuming Guo; Francesco Sera; Veronika Huber; Carl-Friedrich Schleussner; Dann Mitchell; Shilu Tong; Micheline de Sousa Zanotti Staglior Coelho; Paulo Hilario Nascimento Saldiva; Eric Lavigne; Patricia Matus Correa; Nicolas Valdes Ortega; et al. (Climatic Change, 2018)

Annual Phytoplankton Primary Production Estimation in a Temperate Estuary by Coupling PAM and Carbon Incorporation Methods - Jérôme Morelle; Mathilde Schapira; Francis Orvain; Philippe Riou; Pascal Jean Lopez; Olivier Pierre-Duplessix; Emilie Rabiller; Frank Maheux; Benjamin Simon; Pascal Claquin (Estuaries and Coasts, 2018)

Mapping of new resistance (Vr2, Rm1) and ornamental (Di2, pl) Mendelian trait loci in peach - Thierry Pascal; Romain Aberlenc; Carole Confolent; Mathilde Hoerter; Elodie Lecerf; Christophe Tuéro; Patrick Lambert (Euphytica, 2017)

How to estimate exposure when studying the temperature-mortality relationship? A case study of the Paris area - Laura Schaeffer; Perrine de Crouy-Chanel; Vérène Wagner; Julien Desplat; Mathilde Pascal (International Journal of Biometeorology, 2016)

Molecular evolution and transcriptional regulation of the oilseed rape proline dehydrogenase genes suggest distinct roles of proline catabolism during development - Pascal Faës; Carole Deleu; Abdelkader Aïnouche; Françoise Le Cahérec; Emilie Montes; Vanessa Clouet; Anne-Marie Gouraud; Benjamin Albert; Mathilde Orsel; Gilles Lassalle; Laurent Leport; Alain Bouchereau; et al. (Planta, 2015)

A simple indicator to rapidly assess the short-term impact of heat waves on mortality within the French heat warning system - Annamaria Antics; Mathilde Pascal; Karine Laaidi; Vérène Wagner; Magali Corso; Christophe Declercq; Pascal Beaudeau (International Journal of Biometeorology, 2013)

Definition of temperature thresholds: the example of the French heat wave warning system - Mathilde Pascal; Vérène Wagner; Alain Le Tertre; Karine Laaidi; Cyrille Honoré; Françoise Bénichou; Pascal Beaudeau (International Journal of Biometeorology, 2013)

Impact of carrot resistance on development of the Alternaria leaf blight pathogen (Alternaria dauci) - Cora Boedo; Valérie Le Clerc; Mathilde Briard; Philippe Simoneau; Michel Chevalier; Sonia Georgeault; Pascal Poupard (European Journal of Plant Pathology, 2008)

France’s heat health watch warning system - Mathilde Pascal; Karine Laaidi; Martine Ledrans; Elsa Baffert; Céline Caserio-Schönemann; Alain Le Tertre; Jacques Manach; Sylvia Medina; Jérémie Rudant; Pascal Empereur-Bissonnet (International Journal of Biometeorology, 2006)